Preparation and characterization of irradiated magnetic pineapple leaves for paper production - Mohd Sufian, Amirul Azan; Othman, Siti Amira (2021)
Deforestation issues were increased dramatically every year especially in order for the production of paper. This was caused by the demand for making paper and furniture from wood sources. The supply of paper nowadays all depends on the wood. This experiment has been conducted to analyses the viability of magnetic pineapple leaves paper as a replacement for paper production and to analyses the morphology properties of pineapple leaves fiber. The introduction of filler in this research is to alter one or more paper properties such as texture, opacity, brightness, basis weight, dimensional stability, ink absorbency and overall printability. Commonly, most fillers are from clay, titanium dioxide or calcium carbonate. Thus, the ferrite magnet was used as the filler to ensure it has the same properties as the commercial filler. The pineapple leaves fiber then will be undertaking Scanning Electron Microscope (SEM) and Fourier-Transform Infrared Spectroscopy (FTIR) which was used for characterization. Through the characterization under Scanning Electron Microscope (SEM), the surface morphology of the magnetics pineapple leaves paper was changed due to the effect of the gamma radiation and by the degradation on the pineapple leaves fiber. Besides, for FTIR spectroscopy, the result indicated that pineapple leaves fiber was suitable for papermaking where the absorption peak is between 3400 – 2400 cm-1 and shows the presence of O-H and C-H bonds in polysaccharides for both magnetic and non-magnetic irradiated pineapple leaves paper. The magnetics pineapple leaves paper shows the good properties, as well as other commercial papers and this, will give many benefits to reduce the use of wood for making pulp and one of the efforts towards green technology and new invention on papermaking production.